(untitled) (Annals of Medical Research, 2021)
The aim of this study was to investigate the possible toxic effects of sub-chronic doses of acrylamide taken with drinking water on liver tissue and to test the preventive role of 5% organic dried apricot as diet supplement, in female Sprague Dawley rats. Materials and Methods: Forty female Spraque Dawley rats were divided into 4 equal groups as follows: control group (C) animals were fed with normal rat chow and tap water, apricot group (A) animals were fed with chow contain %5 apricot and tap water, acrylamide group (AA) animals were fed with normal rat chow and acrylamide at approximately 500 µg/kg/day via tap water, acrylamide+apricot group (AA+A) animals were fed with chow contain 5% apricot and approximately 500 µg/kg/day acrylamide via drinking water. The study procedure was maintained during 12 weeks experiment period. At the end of the study, samples of liver tissue were collected for biochemical, histopathological and molecular analyses. Results: In this study, comparison of acrylamide group liver tissue GSH levels and GSH-Px activities were found lower when compared to the control group (p 0.05). There were no significant differences between the groups based on GST activity, histopathological results and GST-Pi gene expression mRNA levels (p 0.05). Conclusion: It could be stated that acrylamide, at approximately 500 µg/kg/day, ingested by rats were detoxified by the liver without resulting any liver tissue damage and application of acrylamide with sun-dried organic apricot did not change any significant molecular, histopathological and biochemical parameters in the liver.